2011
DOI: 10.1063/1.3604782
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap engineering of sol-gel synthesized amorphous Zn1−xMgxO films

Abstract: Amorphous Zn1−xMgxO (α-Zn1−xMgxO) ternary alloy thin films across the full compositional range were synthesized by a low-cost sol-gel method on quartz substrates. The amorphous property of the α-Zn1−xMgxO films was verified by x-ray diffraction, and atomic force microscopy revealed a smooth surface with sub-nanometer root-mean square roughness. The current phase segregation issue limiting application of crystalline Zn1−xMgxO with 38% < x < 75% was completely eliminated by growing amorphous films.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…While it is well known that the binaries ZnO and MgO have incompatible crystal structures, Zn-rich ZnMgO (wurtzite B4) and Mg-rich ZnMgO (rocksalt B1) are regularly produced with good crystallinity and smooth surface morphology at different ends of the compositional scale [3,4]. Adding Mg to the ZnO lattice blueshifts the ternary bandgap, while redshifting is accomplished by adding Zn to MgO [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…While it is well known that the binaries ZnO and MgO have incompatible crystal structures, Zn-rich ZnMgO (wurtzite B4) and Mg-rich ZnMgO (rocksalt B1) are regularly produced with good crystallinity and smooth surface morphology at different ends of the compositional scale [3,4]. Adding Mg to the ZnO lattice blueshifts the ternary bandgap, while redshifting is accomplished by adding Zn to MgO [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…However, as the Mg content was increased beyond cycle ratios higher than 7:1, there was a significant reduction in electron mobility presumably due to a large increase in impurity scattering. Furthermore, from photoluminescence spectra, E g increased to 3.38 eV presumably due to the presence of MgO which has a bandgap E g =7.8 eV [8].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, Sadofev et al [18] reported that under non-thermodynamical MBE growth layers with an Mg content up to 40% were realized. Although the ionic radius of Mg 2+ is close to that of Zn 2+ , the crystal structure difference and the large lattice mismatch between ZnO (wurtzite, a = 0.325 nm) and MgO (rock salt, a = 0.422 nm) cause a phase segregation in the Mg x Zn 1 − x O alloy system with Mg compositions between 37% b x b 62% [19]. Thus, some of those work reported that Mg x Zn 1 − x O thin films with hexagonal and cubic phases were grown on various substrates, including glass, sapphire and silicon for the application of ultraviolet optical devices and electron devices according to the Mg content and deposition temperature.…”
Section: Introductionmentioning
confidence: 99%